2020
DOI: 10.1002/jppr.1683
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of Parkinson’s disease in older people

Abstract: Parkinson's disease is a chronic neurodegenerative disorder that mainly affects older people. It is predominately recognised as a movement disorder; however, the non-motor symptoms are gaining increased recognition. Treating both motor and non-motor symptoms can be challenging. Co-morbidities, in particular dementia, polypharmacy and an increased susceptibility to adverse medication effects often necessitate a different approach to management compared to younger patients. In older people, the mainstay of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(220 reference statements)
0
7
0
1
Order By: Relevance
“…Caregiving had a negative impact on their physical, psychological, and social status (66.7%), and 53.8% did not get any help from another one in caregiving (did not have respite care). Table (2) revealed that financial support was the most common support area need (97.4%) reported by PD caregivers, followed by information about Parkinson's disease and about the available community resources (84.6% each), about instruments that facilitate caring and about proper management of disease's motor symptoms (76.9% each). Need to find private time for themselves, and managing negative emotions resulted from caregiving experience were reported by caregivers in significant percent (71.8%, 69.2% respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiving had a negative impact on their physical, psychological, and social status (66.7%), and 53.8% did not get any help from another one in caregiving (did not have respite care). Table (2) revealed that financial support was the most common support area need (97.4%) reported by PD caregivers, followed by information about Parkinson's disease and about the available community resources (84.6% each), about instruments that facilitate caring and about proper management of disease's motor symptoms (76.9% each). Need to find private time for themselves, and managing negative emotions resulted from caregiving experience were reported by caregivers in significant percent (71.8%, 69.2% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the rate of progression of PD varies, along with different combination, range, and severity of symptoms leading to uncertainty in the trajectory of the disease process, which is presently neither reversible nor curable. Multiple treatment options available are used to help the sufferers maintain independence and improve quality of life, not singularly treats all symptoms most come with the risk of significant motor, non-motor, and psychological side effects [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that more regular and targeted dosing is required after 3–5 years of the disease and the progressive loss of independence, dyskinesia, confusion and hallucinations [ 73 , 74 ]. There are also reported side effects associated with pharmacological interventions including oxidative stress in patients, gastrointestinal problems, nausea and peripheral oedema [ 71 , 72 , 75 , 76 , 77 ].…”
Section: Current Therapeutic Approachesmentioning
confidence: 99%
“…This is a topic of increasing relevance and importance, given the increased life expectancy of people with HIV 7 . The second article is a review of the prevention, diagnosis, and management of vitamin B 12 deficiency, which is a common but often under‐recognised problem in older people that may have serious consequences if left untreated 8 . Fittingly, this final article is written by Heidelberg Repatriation Hospital aged‐care pharmacist Nadia Mouchaileh.…”
Section: Therapeutic Area Number Of Articlesmentioning
confidence: 99%